Tax Aspects of Leaving the European Union - Wiman, Bertil (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The article deals with some income tax in particular corporate income tax aspects of the United Kingdom leaving the European Union, from a Swedish perspective.